2017
DOI: 10.30813/bmj.v13i1.247
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Layanan-E, Kepuasan-E, Dan Kepercayaan-E Terhadap Kesetiaan-E Pada Gojek

Abstract: ABSTRAKBisnis penyedia layanan daring berkembang dengan pesat saat ini dan diikuti dengan persaingan sengit antar penyedia layanan daring. Merupakan hal yang sangat penting bagi mereka untuk bertahan dan menang dalam persaingan bisnis ini. Untuk itu perlu diidentifikasikan mengenai apa saja kualitas layanan dari situs tersebut yang menjadi perhatian pelanggan, mengetahui seberapa jauh kepuasan, seberapa dalam tingkat kepercayaan dan seberapa jauh kesetiaan pelanggan terhadap situs penyedia layanan daring terse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…The results of the H3a hypothesis test are also different from Setyaji and Ngatno (2016) and Purba (2017) who find that service quality has a significant direct effect on customer loyalty. The results of the H3b hypothesis test are different from Berlianto (2017) who concluded that e-service quality does not affect the e-satisfaction of GO-JEK customers in Jakarta.…”
Section: Figure 1 Hypothesis Test Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…The results of the H3a hypothesis test are also different from Setyaji and Ngatno (2016) and Purba (2017) who find that service quality has a significant direct effect on customer loyalty. The results of the H3b hypothesis test are different from Berlianto (2017) who concluded that e-service quality does not affect the e-satisfaction of GO-JEK customers in Jakarta.…”
Section: Figure 1 Hypothesis Test Resultscontrasting
confidence: 83%
“…Researchers at Sitinjak (2018), Setyaji and Ngatno (2016) and Berlianto (2017) found that there was a significant effect of customer satisfaction on GO-JEK customer loyalty. According to Kotler and Keller (2009) satisfaction is the level of one's feelings after comparing the performance (or results) that he feels compared to his expectations.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Customer loyalty is influenced by factors such as physical evidence/facilities, location, product and customer satisfaction (Farida et al, 2016), Perceived Value and customer satisfaction (Putri et al, 2018), Customer Relationship Management, and customer satisfaction E-Service Quality, customer trust and satisfaction (Berlianto, 2017), service quality and price (Sugiarsih Duki Saputri, 2019), promotion and consumer satisfaction (Jati Prabowo & Sitio, 2020) A pre-research survey was conducted from October 7, 2020, to October 8, 2020, on 20 respondents who are online food ordering customers. The results of the survey data processing showed that the three most dominant variables got the answer DO NOT AGREE, namely: promotion, product quality, and perceived value with gains of 37.50%, 30%, and 27.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%